Measuring Intra-Generational Redistribution in PAYG Pension Schemes - Jonas Klos; Tim Krieger; Sven Stöwhase (Center for Economic Studies and ifo Institute (CESifo), 2020)
In this paper, we propose a novel index for measuring intra-generational redistribution in pay-as-you-go pension schemes. Our index solely requires information on contributions and pension benefits of retirees, enabling us to measure intra-generational redistribution isolated from possible inter-generational redistribution. We use contribution records of approx. 100,000 German individuals, who progressed into retirement in 2007-2015, to measure the level of intra-generational redistribution in the German statutory pension scheme (GRV). A recent reform of childcare benefit provision, which became effective in 2014, confirms the predictions of our index. The reform introduced additional benefits for a subgroup of substantial size of German mothers, due to which the index value for women, but not for men jumps up. Our findings suggests that GRV fulfils the ideal of a Bismarckian pension system without intra-generational redistribution for men, while women benefit from intra-generational redistribution.
Keywords: H55; D31; C55; 330; PAYG pension systems; intra-generational redistribution; Beveridge vs. Bismarck; index; microdata; Germany